A Photoionization Method for Estimating Black Hole Masses in Quasars. Issue Volume 14:Issue S342(2018) (May 2018) - Alenka Negrete, C.; Dultzin, Deborah; Marziani, Paola; Sulentic, Jack W.; Martínez-Aldama, M. L.
Abstract: We present a method that uses photoionization codes (CLOUDY) to estimate the supermassive black hole masses ( M BH ) for quasars at low and high redshift. This method is based on the determination of the physical conditions of the broad line region (BLR) using observational diagnostic diagrams from line ratios in the UV. We also considered that the density and metallicity of the BLR in quasars at high z could be different from those at the nearby Universe. The computed black hole masses obtained using this method are in agreement with those derived from the method of reverberation mapping.